Cytoprotective effects of α-linolenic acid, eicosapentaenoic acid, docosahexaenoic acid, oleic acid and α-tocopherol on 7-ketocholesterol – Induced oxiapoptophagy: Major roles of PI3-K / PDK-1 / Akt signaling pathway and glutathione peroxidase activity in cell rescue - Aline Yammine; Imen Ghzaiel; Vivien Pires; Amira Zarrouk; Omar Kharoubi; Hélène Greige-Gerges; Lizette Auezova; Gérard Lizard; Anne Vejux (Current Research in Toxicology, 2024)
On murine N2a cells, 7-ketocholesterol induced an oxiapotophagic mode of cell death characterized by oxidative stress (reactive oxygen species overproduction on whole cells and at the mitochondrial level; lipid peroxidation), apoptosis induction (caspase-9, −3 and −7 cleavage, PARP degradation) and autophagy (increased ratio LC3-II / LC3-I). Oxidative stress was strongly attenuated by diphenyleneiodonium chloride which inhibits NAD(P)H oxidase. Mitochondrial and peroxisomal morphological and functional changes were also observed. Down regulation of PDK1 / Akt signaling pathways as well as of GSK3 / Mcl-1 and Nrf2 pathways were simultaneously observed in 7-ketocholesterol-induced oxiapoptophagy. These events were prevented by α-linolenic acid, eicosapentaenoic acid, docosahexaenoic acid, oleic acid and α-tocopherol. The inhibition of the cytoprotection by LY-294002, a PI3-K inhibitor, demonstrated an essential role of PI3-K in cell rescue. The rupture of oxidative stress in 7-ketocholesterol-induced oxiapoptophagy was also associated with important modifications of glutathione peroxidase, superoxide dismutase and catalase activities as well as of glutathione peroxidase-1, superoxide dismutase-1 and catalase level and expression. These events were also counteracted by α-linolenic acid, eicosapentaenoic acid, docosahexaenoic acid, oleic acid and α-tocopherol. The inhibition of the cytoprotection by mercaptosuccinic acid, a glutathione peroxidase inhibitor, showed an essential role of this enzyme in cell rescue. Altogether, our data support that the reactivation of PI3-K and glutathione peroxidase activities by α-linolenic acid, eicosapentaenoic acid, docosahexaenoic acid, oleic acid and α-tocopherol are essential to prevent 7KC-induced oxiapoptophagy.